Time-Delay Circuits for Fluidic Oscillators and Pulse Shapers - Václav Tesař (Energies, 2019)
Fluidic signals transferred between mutually communicating components of fluidic circuits are nowadays still often in the format of continuously varied value of pressure or flow rate. Especially when transported over longer distances, these simple signals may easily deteriorate due to varying properties they meet in the transmission. An example are friction losses dependent on local temperature. A solution to this signal corruption problem is to encode the signals into flow pulses. Their parameters (such as the number of pulses in a delivered pulse cluster) much less deteriorating during transfer are derived from the time delays generated in delay circuits and oscillators. This paper surveys the basic physical aspects of the fluidic pulse generation and shaping, also presents some examples of circuit design.